‘A shadow of me old self’: The impact of image-based sexual abuse in a digital society - Huber, Antoinette (International review of victimology, 2023)
This article sheds a new light on the impact of image-based sexual abuse (IBSA) on women. Drawing on findings from 17 in-depth interviews, it details the emotional, physical and social impact of this online victimisation, and how the impact of IBSA manifests in women’s everyday lives. By also using these findings as a basis to examine online victimisation more broadly, this article brings to the fore broader considerations of how technology is facilitating a mutation in forms of sexual violence causing victims to encounter impacts which are specific to, or amplified by, technology. Therefore, it calls for greater attention to be paid to the impacts of IBSA and more research into how the relationships between the online and offline worlds require us to change our understanding of victimisation in an ever-increasing digital society.